Geographically differentiated NGA deployment - Markos Tselekounis; Eirini Xylogianni; Dimitris Varoutas; Drakoulis Martakos (International Telecommunications Society (ITS), 2013)
This paper studies the incentives of an unregulated monopolist to undertake the socially optimal investment in NGA networks when it takes into account the fact that the NGA deployment is a two-dimensional investment decision concerning both the quality (or equivalently, technology) and the geographic coverage. It is found that both the privately and the socially optimal investment decisions result in a geographically differentiated NGA deployment implying that different quality NGA networks are deployed in different geographic areas. In particular, NGA networks of higher (lower) quality are deployed in the more (less) densely populated geographic areas. Although such geographically differentiated NGA investment leads the monopolist to provide a nationwide NGA deployment, it is found that the monopolist underinvests compared to the socially optimal levels of both technology and geographic coverage. In addition, since the objectives of the Europe 2020 Strategy concern both the NGA technology and the NGA coverage, this paper shows that the first objective of providing all Europeans with access to much higher internet speeds of above 30 Mbps is feasible when the demand for NGA-based services is significantly elastic, whereas the second objective of providing internet connection speeds of 100 Mbps to 50% or more of European households is not a feasible goal.
Keywords: 330; broadband; geographic areas; investment incentives; next generation access networks; telecommunications